Key Trends in Implementing the Fund's Transparency Policy. (Policy Papers; Policy Paper ;, 2014)
At the time of the 2005 review of the Fund's transparency policy, it was agreed that information on key trends in implementation of the transparency policy would be circulated to the Board regularly, along with lists indicating the publication status of reports discussed by the Board. The set of tables provided in this report updates the last Key Trends with information on documents issued to the Board through December 2013.